2017
DOI: 10.1016/j.fitote.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenylnaphthalenes and a polyoxygenated cyclohexene from the stem and root extracts of Uvaria cherrevensis (Annonaceae)

Abstract: Three new 2-phenylnaphthalene derivatives, cherrevenaphthalenes A-C (1-3), and a new polyoxygenated cyclohexene derivative, (-)-uvaribonol F (4) together with six known compounds, 5-10, were isolated from the stem and root extracts of Uvaria cherrevensis (Annonaceae). The structures of all isolated compounds were elucidated by spectroscopic analysis. The structures of 3 and 4 were further confirmed by single crystal X-ray diffraction methods. Compound 2 exhibited modest antiplasmodial activity against the P. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In contrast, the compounds 3, 7, 14 and 15 were not cytotoxic against either cell line at 50 µM. Overall, most of thesecompounds were more cytotoxic than those previously isolated from the stem and root extract of this plant[5].In conclusion, four new C-benzyl flavonoids (1-4) have been isolated, with compounds showing significant cytotoxicities against KB and Vero cells. While C-benzyl flavonoids…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…In contrast, the compounds 3, 7, 14 and 15 were not cytotoxic against either cell line at 50 µM. Overall, most of thesecompounds were more cytotoxic than those previously isolated from the stem and root extract of this plant[5].In conclusion, four new C-benzyl flavonoids (1-4) have been isolated, with compounds showing significant cytotoxicities against KB and Vero cells. While C-benzyl flavonoids…”
mentioning
confidence: 61%
“…Previous phytochemical studies of this plant reported the isolation of alkaloids, flavonoids, naphthalene derivatives, polyoxygenated cyclohexenes and terpenoids [3][4][5][6]. Some of these compounds were reported to have antimalarial, antimicrobial and cytotoxic activities [3,5,6]. In a previous report, we found 2phenylnaphthalene derivatives, polyoxygenated cyclohexenes and flavonoids from the stems and roots extracts of this plant [5].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations